1997
DOI: 10.1002/(sici)1098-1063(1997)7:1<58::aid-hipo6>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Model of spatio-temporal propagation of action potentials in the Schaffer collateral pathway of the CA1 area of the rat hippocampus

Abstract: There is a sharp contrast between the profuse in vivo axonal arborization of CA3 pyramidal cells in the CA1 area and the low probability of finding pairs of connected CA3‐CA1 pyramidal cells in vitro. These anatomical differences contribute to a connectivity argument for discrepancies between electrophysiological data recorded in vitro and in vivo. In order to investigate this issue, we have developed a realistic computer model of the Schaffer collateral pathway of the hippocampus and analyzed the spatio‐tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Indeed, prior modeling studies of idealized networks indicated the importance of altered network architecture in epileptogenesis (Buzsáki et al 2004;Netoff et al 2004;Percha et al 2005). However, to test the role of structural changes actually taking place during epileptogenesis, the network models must be strongly data driven, i.e., incorporate key structural and functional properties of the biological network (Ascoli and Atkeson 2005;Bernard et al 1997;Traub et al 2005a,b). Such models should also be based on as realistic cell numbers as possible, to minimize uncertainties resulting from the scaling-up of experimentally measured synaptic inputs to compensate for fewer cells in reduced networks.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, prior modeling studies of idealized networks indicated the importance of altered network architecture in epileptogenesis (Buzsáki et al 2004;Netoff et al 2004;Percha et al 2005). However, to test the role of structural changes actually taking place during epileptogenesis, the network models must be strongly data driven, i.e., incorporate key structural and functional properties of the biological network (Ascoli and Atkeson 2005;Bernard et al 1997;Traub et al 2005a,b). Such models should also be based on as realistic cell numbers as possible, to minimize uncertainties resulting from the scaling-up of experimentally measured synaptic inputs to compensate for fewer cells in reduced networks.…”
Section: Introductionmentioning
confidence: 99%
“…Computer simulations of epileptiform activity have provided powerful insight into mechanisms of neuron dynamics (Traub and Llinas, 1979;Traub et al, 1985Traub et al, , 1991Warman et al, 1994;Pinsky and Rinzel, 1994;Bernard et al, 1997). Based on the available voltage-clamp data and current-clamp data for HPCs in normal solution, isolated or coupled CA1 and CA3 HPCs have previously been simulated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…In the model, we used 23,500 CA1 principal cells. This is an estimate of the number of principal cells in a square millimeter patch given that there are approximately 320,000 principal cells in 13.6 square millimeters of the whole rat CA1 (Bernard and Wheal, 1994; Bernard et al, 1997). We assumed that at the beginning of a 20 ms gamma period, all CA1 principal cells were in the same state.…”
Section: Methodsmentioning
confidence: 99%